O Direito Penal europeu à luz do princípio da necessidade – o caso do abuso de mercado - Rodrigues, Anabela Miranda (2017)
The aim of this study is to assess the legitimacy of the Market Abuse Directive (2014/57/EU), from the point of view of the criterion of the need for criminal intervention in the terms set out in Article 83 (2) TFEU. The question is qualitatively different from the one posed at the national level, which is linked to the principle of subsidiarity of Union law. It requires a ‘constitutional’ and ‘restrictive’ interpretation of that rule by means of ‘evidence’, in concrete rather than abstract terms, of the ‘essential’ nature of criminal proceedings in order to ensure the effectiveness of Union law in an area subjected to harmonization measures. The criterion was already enshrined in the jurisprudence of the CJEU, which called for ‘clear factual evidence’ in its densification. The analysis of the arguments in the Proposal of the Directive concludes that they are vague, generic and symbolic and do not give substance to the need for criminal intervention at European level to combat serious fraud in the financial market regime.